Shame, Poverty and Development Studies. (29th August 2017) - Engel, Susan
Abstract: Development studies have been slow to explore and embrace the burgeoning field of emotions research, yet increasingly development interventions are adopting emotions‐based strategies, including the deliberate use of shaming. This article reviews the implications of a new three volume collection on poverty and shame for development studies, arguing that it offers a fruitful avenue for research that focuses on understanding the lived experiences, perceptions and feelings of the poor, as opposed to conventional uncompassionate qualitative analysis.